Performance Evaluation of Porous Asphalt Mixtures Incorporating Cotton Cloth Ash as Filler Based on Marshall Characteristics and Permeability - Dicky Dwi Firmansyah; Aditya Rizkiardi; Nurani Hartatik (Asosiasi Dosen Muda Indonesia, 2026)
Porous asphalt is designed to improve surface drainage and reduce water accumulation; however, its performance depends on the balance between mechanical strength and permeability. The use of alternative filler materials, particularly textile-derived waste such as cotton cloth ash, remains limited. Objective: This study aims to evaluate the performance of porous asphalt mixtures incorporating cotton cloth ash as a substitute filler, focusing on optimum asphalt content, Marshall characteristics, and permeability behavior. Methodology: An experimental quantitative approach was conducted in a laboratory. The mixture design followed the Australian Asphalt Pavement Association (AAPA, 2004) method. Data were obtained through material testing, Marshall testing, and permeability testing. Key parameters analyzed included Void in Mix (VIM), Stability, Flow, Marshall Quotient (MQ), Cantabro Loss (CL), Asphalt Flow Down (AFD), and permeability. Findings: The Optimum Asphalt Content (OAC) was identified at 4.80%. The best mechanical performance occurred at 4.5%–5% asphalt content, with maximum stability of 832 kg and MQ of 530 kg/mm. Permeability increased with asphalt content, reaching 0.20 liter/second at 6%, indicating improved drainage but reduced structural performance at higher binder levels. Implications: The results highlight the importance of optimizing asphalt content to achieve a balance between mechanical strength and hydraulic performance in porous asphalt design. Originality: This study introduces cotton cloth ash as an alternative filler, demonstrating its feasibility in maintaining functional and structural performance while supporting sustainable pavement materials.